2020
DOI: 10.1186/s12891-020-03679-3
|View full text |Cite
|
Sign up to set email alerts
|

LUMINOUS database: lumbar multifidus muscle segmentation from ultrasound images

Abstract: Background Among the paraspinal muscles, the structure and function of the lumbar multifidus (LM) has become of great interest to researchers and clinicians involved in lower back pain and muscle rehabilitation. Ultrasound (US) imaging of the LM muscle is a useful clinical tool which can be used in the assessment of muscle morphology and function. US is widely used due to its portability, cost-effectiveness, and ease-of-use. In order to assess muscle function, quantitative information of the LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In detail, in 2019 Tack [14] focused on musculoskeletal medicine in general, and determined in which fields AI had reached human prediction levels; in 2020, Azimi et al [15] focused on the use of NNs for the treatment of the whole spine; in 2019, Galbusera et al [1] described the application of AI to problems related to the whole spine; finally, in 2016 Yao et al [16] performed a multi-center milestone comparative study for vertebral segmentation methods based on CT images. Two articles presenting databases were also found: LUMINOUS, which is a database of ultrasound images from 109 patients for multifidus muscle segmentation [17], and MyoSegmentum, which includes MRI images of 54 patients for the segmentation of lumbar muscles and vertebral bodies [18].…”
Section: Resultsmentioning
confidence: 99%
“…In detail, in 2019 Tack [14] focused on musculoskeletal medicine in general, and determined in which fields AI had reached human prediction levels; in 2020, Azimi et al [15] focused on the use of NNs for the treatment of the whole spine; in 2019, Galbusera et al [1] described the application of AI to problems related to the whole spine; finally, in 2016 Yao et al [16] performed a multi-center milestone comparative study for vertebral segmentation methods based on CT images. Two articles presenting databases were also found: LUMINOUS, which is a database of ultrasound images from 109 patients for multifidus muscle segmentation [17], and MyoSegmentum, which includes MRI images of 54 patients for the segmentation of lumbar muscles and vertebral bodies [18].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding segmentation, several prior studies have investigated cardiac and fetal systems [ 14 , 15 , 16 ]; however, there are very few deep learning studies on the musculoskeletal system. Belasso et al [ 17 ] showed that US images of the lumbar multifidus muscle could be segmented automatically. Nevertheless, few studies have segmented long-axis images of peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of persistent inflammation following skeletal muscle injury is also one of the clinical concerns that need urgent attention. Generally, 50 % of acute injuries become chronic [ 6 , 7 ]. A multitude of causes can alter skeletal muscle homeostasis, resulting in skeletal muscular atrophy, such as diabetes, cancer and chronic obstructive pulmonary disease, weightlessness, denervation disuse state, fasting, and aging [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%